Applying the Hedgehog Concept to Transform Undergraduate Medical Education. (April 2019) - Ginzburg, Samara B.; Willey, Joanne M.; Bates, Carole; Santen, Sally A.; Battinelli, David; Smith, Lawrence
Abstract : As the U.S. health care system changes and physician responsibilities shift, medical educators must reconsider how best to prepare medical school graduates for the future practice of medicine. Thoughtful reexamination of the goals of undergraduate medical education (UME) and the roles of educators, medical students, and physicians is warranted to ensure that they align with evolving health care environments and delivery systems. In this Invited Commentary, the authors apply Jim Collins's "hedgehog concept" from Good to Great —a business-world framework designed to transform companies—to UME. The hedgehog concept is defined by the intersection of an organization's passion, area of expertise, and economic and resource engines. Focusing on this single concept can guide key decisions, reject what does not align conceptually, and drive overall organizational success. The authors use the hedgehog concept to frame the programmatic development of the Donald and Barbara Zucker School of Medicine at Hofstra/Northwell (Zucker SOM), a millennial medical school, as an organization with the passion to develop innovative UME curricula by challenging the status quo; the drive to be the best at leveraging health system resources to train graduates to excel in systems-based care; and the economic and resource engine of faculty time, financial and infrastructure support, and reputation building. The success of this approach is assessed at Zucker SOM through student and graduate outcomes data. The authors suggest that this hedgehog concept is generalizable to other UME programs whose leaders seek to transform medical education to meet 21st-century workforce and health care delivery needs.